Samuel Potter papers - Potter, Samuel
Correspondence, portion of a diary (1863), and legal and military papers. Primarily correspondence between Potter and his wife, Sophie, relating chiefly to military camp life during his service with the 140th Regiment, Pennsylvania Volunteer Infantry.
In part, typewritten transcripts.
Union army soldier.
Collection material in English.
Keywords: Potter, Sophie -- Correspondence; United States. -- Army -- Military life; United States. -- Army. -- Pennsylvania Infantry Regiment, 140th (1862-1865); Pennsylvania -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Soldiers